Answer:
Options (2) and (3)
Step-by-step explanation:
Let,
-8 + 8i√3 = a² + b²i² + 2abi
-8 + 8i√3 = a² - b² + 2abi
By comparing both the sides of the equation,
a² - b² = -8 -------(1)
2ab = 8√3
ab = 4√3 ----------(2)
a =
By substituting the value of a in equation (1),
48 - b⁴ = -8b²
b⁴ - 8b² - 48 = 0
b⁴ - 12b² + 4b² - 48 = 0
b²(b² - 12) + 4(b² - 12) = 0
(b² + 4)(b² - 12) = 0
b² + 4 = 0 ⇒ b = ±√-4
b = ± 2i
b² - 12 = 0 ⇒ b = ±2√3
Since, a =
For b = ±2i,
a =
=
=
But a is real therefore, a ≠ ±2i√3.
For b = ±2√3
a =
a = ±2
Therefore, (a + bi) = (2 + 2i√3) and (-2 - 2i√3)
Options (2) and (3) are the correct options.
Answer:
81 cm^2
Step-by-step explanation:
Side = perimeter / 4 = 36/4 = 9 cm
area = side^2 = 9^2 = 81 cm^2
Answer:
±6
Step-by-step explanation:
Given the mathematical expression;
√36 < √42 < √49
But, √36 = 6 * 6 = 6²
√49 = 7 * 7 = 7²
Simplifying further, we would substitute the new values respectively;
±[6] < √42 < ±[7]
Therefore, evaluating √36 is equal to ±6.
340+.06(sales)
340+.06(660)
$379.60
I dont know the answer lol but imma say B